Development and Implementation of an Intelligent Monitoring System for Spanning Construction of Low-Voltage Transmission Lines - Qiu, Xiaocong (Journal of Computer Science and Software Applications, 2022)
To enhance the safety and automation in the construction of transmission lines with voltage levels of 110 kV and below, an intelligent monitoring system for spanning frames has been developed. This system is based on Programmable Logic Controllers (PLC) and configuration software. It facilitates real-time monitoring and early warning of various parameters, including height, inclination, and wind speed at the construction site. Additionally, it controls a series of actions such as synchronous lifting and spanning of the crossing pole, as well as the distribution and collection of insulating mesh. The system employs a distributed structure comprising a central monitoring center and four substations, achieving distributed hybrid networking through the integration of wireless communication, serial communication, and 4G communication.